HUBUNGAN STRES KERJA TERHADAP PENERIMAAN PERILAKU DISFUNGSIONAL AUDIT DENGAN LOCUS OF CONTROL DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL PEMODERASI (Studi Empiris pada Auditor di BPKP RI Perwakilan Provinsi Riau dan Kepulauan Riau) - Anggi Eka Puspita; Yesi Mutia Basri; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to analyzed the effect of job stress on the acceptance of dysfunctional audit behavior, focussed on personal auditor characteristics viewed from internal locus of control and external locus of control, and organizational commitment as one of auditor's work attitude. This research was conducted on auditors working in State Development Audit Agency (Badan Pengawas Keuangan dan Pembangunan-BPKP) Riau and Riau Islands Province. The sample in this study amounted to 78 auditors. Sampling method in this research was convenience sampling technique. This research was collected data by distributing questionnaire. Statistic method used in this research were Linear Regression Analysis and Moderated Regression Analysis (MRA). The test results showed that job stress have a posstive and significant effect on acceptance of dysfunctional audit behavior. Internal locus of control were not able to moderated relation of job stress to acceptance of dysfunctional audit behavior. But, external locus of control and organizational commitmentcould be moderating relation of job stress to acceptance of dysfunctional audit behavior. External locus of control had strengthen relation of job stress and acceptance of dysfunctional audit behavior. Organizational commitment was able to weaken the relation of work stress to acceptance of dysfunctional audit behavior.Keywords: Internal locus of control, external locus of control, organizational commitment, acceptance of dysfunctional audit behaviour